Molecular Mechanisms and Potential New Therapeutic Drugs for Liver Fibrosis - Wang, Fa-Da; Zhou, Jing; Chen, En-Qiang (Frontiers in Pharmacology, 2022)
Liver fibrosis is the pathological process of excessive extracellular matrix deposition after liver injury and is a precursor to cirrhosis, hepatocellular carcinoma (HCC). It is essentially a wound healing response to liver tissue damage. Numerous studies have shown that hepatic stellate cells play a critical role in this process, with various cells, cytokines, and signaling pathways engaged. Currently, the treatment targeting etiology is considered the most effective measure to prevent and treat liver fibrosis, but reversal fibrosis by elimination of the causative agent often occur too slowly or too rarely to avoid life-threatening complications, especially in advanced fibrosis. liver transplantation as the only treatment option in the end-stage, leaving us with an urgent need for new therapies. An in-depth understanding of the mechanisms of liver fibrosis could identify new targets for the treatment. Most of the drugs aimed at molecular mechanisms are still in pre-clinical trials and there are hardly any definitive anti-fibrotic chemical or biological drugs available for clinical use. In this review, we will summarize the pathogenesis of liver fibrosis, focusing on the role of key hepatocyte populations, associated mechanisms and signalling pathways, and summarize various therapeutic measures or drugs that have been approved for clinical use or are in the research stage.